Unveiling the perfect workout: exercise modalities and dosages to ameliorate adipokine dysregulation in individuals with overweight and obesity: a systematic review with pairwise, network, and dose–response meta-analyses - Wang, Hai; Wang, Hao; Zhan, Enyan; Liu, Xiaodong (Frontiers in Nutrition, 2025)
BackgroundObesity is commonly associated with dysregulation of adipokines, particularly characterized by elevated leptin levels and reduced adiponectin levels. These abnormalities are closely linked to an increased risk of developing type 2 diabetes mellitus (T2DM), cardiovascular diseases, and certain cancers.ObjectiveTo systematically evaluate the effects of different exercise modalities—AE, RT, COM, HIIT—and their dosages on the regulation of adipokines (leptin and adiponectin) in individuals with overweight and obesity.MethodsA comprehensive literature search was conducted across Cochrane, Embase, PubMed, Web of Science, and EBSCO databases for randomized controlled trials (RCTs) published between 2000 and January 2025. A random-effects Bayesian model was applied to perform pairwise meta-analysis, network meta-analysis, and dose–response meta-analysis to compare the effects of various exercise interventions and their respective doses. Additionally, meta-regression analysis was conducted to explore potential moderating effects of age, sex, body mass index (BMI), and body fat percentage on the intervention outcomes.ResultsA total of 61 RCTs involving 3,069 participants were included. The network meta-analysis showed that all exercise interventions significantly increased adiponectin levels, with HIIT yielding the most pronounced effect (SMD = 0.85, 95% CrI: 0.24–1.45; SUCRA = 68%), followed by RT, AE, and COM. For leptin levels, COM was the most effective intervention (SMD = −0.99, 95% CrI: −1.48 to −0.51; SUCRA = 84%), followed by AE and HIIT, while RT did not demonstrate a statistically significant effect. Dose–response analysis indicated an inverted U-shaped relationship between exercise and improvements in adiponectin, with the optimal effective dose around 880 MET-min/week. In contrast, a negative linear relationship was observed between exercise and leptin, with notable improvements starting at approximately 770 MET-min/week. The dose–response relationships varied by exercise type. Meta-regression further revealed that age and BMI were positively associated with improvements in adiponectin, while BMI and body fat percentage were positively correlated with improvements in leptin. However, age was negatively associated with changes in leptin. No significant moderating effect of sex was observed on changes in adipokine levels.ConclusionThis study provides moderate-quality evidence supporting the effectiveness of HIIT, COM, and AE in improving adipokine profiles among individuals with overweight and obesity, although the effects differ by exercise modality. The well-defined dose–response relationships underscore the importance of individualized exercise prescriptions, with moderate to high weekly doses (approximately 800–1,300 MET-min/week) recommended to optimize endocrine and metabolic health. Future research should further investigate inter-individual variability in response to exercise interventions and their long-term clinical benefits.Systematic review registrationCRD420251010709, https://www.crd.york.ac.uk/PROSPERO/.